IMPROVING STUDENTS’ READING COMPREHENSION THROUGH THE USE OF NUMBERED HEAD TOGETHER (NHT) TECHNIQUE - Yustina Selong (Journal of English Educational Study (JEES), 2019)
This research is a Classroom Action Research (CAR). Numbered Head Together (NHT) was used as the technique to improve students’ reading comprehension which was conducted in two cycles. The subject of this research were the tenth grade students of social 3 class in SMA Negeri 2 Sungai Kakap in the academic year of 2017/2018. The class consisted of 35 students. The data collection used observation and measurement technique. The results showed that Numbered Head Together (NHT) technique could improve students’ ability in reading comprehension. Moreover, it could influence the students’ attention, and also motivated them in learning activities as the result of the groups’ discussion. Through the use of Numbered Head Together (NHT) technique, the students were able to participate in teaching learning process. They became serious in listening to the teacher’s explanations and worked cooperatively with their friends in each group. They were also more active, enthusiastic, and more confident in following class activities which resulted on the better atmosphere of the classroom that was more enjoyable and alive. Keywords:Reading Comprehension, Numbered Head Together and Classroom Action Research